EFFECT OF CASH TURNOVER, RECEIVABLE TURNOVER, AND INVENTORY TURNOVER ON PROFITABILITY: PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Mochamad Ihza Prasena; Sri Zulaihati; Mardi Mardi (Yayasan Education and Social Center, 2022)
The study used secondary data obtained from the web www.idx.co.id. The analysis used in this study was using multiple linear regressions used to examine the influence of independent variables on dependent variables, a study population of 182 companies and a research sample of 48 companies selected using purposive sampling techniques. The results showed that partially the cash turnover variable had an influence on profitability. Variables perputarn receivables have no influence on profitability and inventory turnover variables have an influence on profitability. Simultaneously variable cash turnover, receivable turnover and inventory turnover have an influence on the proditability of manufacturing companies. The results of the determination coefficient test of 9.1% while the remaining 90.9% were explained by other variables not studied in the study